2004
DOI: 10.1021/ef030148e
|View full text |Cite
|
Sign up to set email alerts
|

New Pretreatment Methods Combining a Hot Water Treatment and Water/Acetone Extraction for Thermo-Chemical Conversion of Biomass

Abstract: New pretreatment methods were developed for separating hemicellulose, cellulose, and lignin from biomass for their efficient use in the thermo-chemical conversion of each component. One method is basically a two-step process. Biomass treated in hot water at 180 °C was extracted in a flowing stream of water/acetone mixture under 10 MPa at 230 °C. Through the hot water treatment, hemicellulose in biomass was successfully recovered as saccharides, leaving lignin and cellulose as a solid. Through the sequential ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 17 publications
0
47
0
Order By: Relevance
“…There are several methods applied to separate the hemicellulose from the wood materials such as acid pretreatments (Nguyen, Tucker, Keller, & Eddy, 2000), alkaline extraction (Egüés, Sanchez, Mondragon, & Labidi, 2012), liquid hot-water extraction (Hasegawa, Tabata, Okuma, & Mae, 2004), steam treatment (Palm & Zacchi, 2003), ionic liquid extraction (Froschauer et al, 2013) and so on. These methods are available to extract the hemicellulose.…”
Section: Structure Of Hemicellulosementioning
confidence: 99%
“…There are several methods applied to separate the hemicellulose from the wood materials such as acid pretreatments (Nguyen, Tucker, Keller, & Eddy, 2000), alkaline extraction (Egüés, Sanchez, Mondragon, & Labidi, 2012), liquid hot-water extraction (Hasegawa, Tabata, Okuma, & Mae, 2004), steam treatment (Palm & Zacchi, 2003), ionic liquid extraction (Froschauer et al, 2013) and so on. These methods are available to extract the hemicellulose.…”
Section: Structure Of Hemicellulosementioning
confidence: 99%
“…Hot water extraction was the most widely used traditional technology for extraction of polysaccharides (Dong et al, 2009;Cai et al, 2008;Qiao et al, 2010;Leppanen et al, 2011;Hartonen et al, 2007;Hasegawa et al, 2004;Sattler et al, 2008;Ando et al, 2004;Yu et al, 2008). For example, Cai et al (2008) investigated the effects of hot water extraction parameters on the yield of polysaccharides from Opuntia milpa alta and obtained the optimal condition.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, water at 393K could be used to extract hemicelluloses from wood (Sattler et al, 2008). Hasegawa et al (2004) reported that hemicelluloses have been recovered from Japanese apricot trees at 453K. Furthermore, naringenin and other antioxidants have been extracted successfully from aspen knotwood at 423K (Hartonen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Subcritical organic solvents such as compressed hot water/ethanol and water/acetone were used for the extraction of biomass from woods 16,17 . The former was useful in extraction of nonylphenol polyethoxy carboxylates from industrial and municipal sludge 18 , and the latter was also used for organosolv pulping of wheat straw to obtain paper sheets 19 .…”
Section: Introductionmentioning
confidence: 99%